How Intelligent Transformation Empowers Innovation Quality Improvement in Manufacturing Enterprises: A Resource Orchestration Perspective - Xinyi Liu; Qinghao Zheng; Yang Deng; Zongjun Wang (Systems)
The rise of Industry 4.0 has led more manufacturers to embrace the concept of intelligent transformation. Understanding this relationship improves both transformation efficiency and the quality of innovation. This study, based on resource orchestration theory, empirically tests a sample of Chinese A-share listed manufacturing companies from 2007 to 2022. The key findings are as follows: (1) intelligent transformation significantly enhances the innovation quality of manufacturing firms, particularly in the eastern region, non-state-owned enterprises, and non-high-tech enterprises; (2) intelligent transformation, as a vital means of resource orchestration, optimizes resource allocation, thereby strengthening corporate financing, organizational resilience, and risk-taking capabilities, ultimately empowering the improvement in innovation quality; (3) the three sub-dimensions of intelligent transformation—intelligent sensing technology, intelligent production and manufacturing, and intelligent strategic layout—all significantly contribute to the enhancement of innovation quality in manufacturing firms. These conclusions provide new insights for manufacturing enterprises to utilize intelligent transformation for resource orchestration and offer valuable implications for the improvement in their innovation quality.